The anatomy of Harpo Marx - Koestenbaum, Wayne (University of California Press, 2012)
The Anatomy of Harpo Marx is a luxuriant, detailed play-by-play account of Harpo Marx's physical movements as captured on screen. Wayne Koestenbaum guides us through the thirteen Marx Brothers films, from The Cocoanuts in 1929 to Love Happy in 1950, to focus on Harpo's chief and yet heretofore unexplored attribute-his profound and contradictory corporeality. Koestenbaum celebrates the astonishing range of Harpo's body-its kinks, sexual multiplicities, somnolence, Jewishness, "cute" pathos, and more. In a virtuosic performance, Koestenbaum's text moves gracefully from insightful analysis to cul